“They Don't Have the Time for That, Participating in Politics” - How Local Politicians Interpret Political Integration in the USA - Jessica Kuhlmann (Journal of International Migration and Integration, 2025)
Political integration is an important aspect of immigrant integration because it strengthens ties with the host country's political institutions. In particular, the local level is often the first step for immigrants to become politically engaged as they feel that they have a stake in the city, and, indeed, many diverse cities position themselves as advocates of immigrant rights. However, we know little about how local politicians interpret the political integration of immigrants in their communities. To identify key patterns in their interpretations, I conducted 20 qualitative interviews with local politicians and administrative employees in Maryland and Washington, D.C. and analyzed them using Bohnsack's documentary method. Specifically, I compare immigrant and non-immigrant local politicians and administrative employees. Overall, immigrant and non-immigrant local politicians differ in their views of the relationship between immigrants and political integration. While immigrant local politicians conceive political integration and other forms of integration, such as labor market integration, as equally important, non-immigrant politicians view political integration as subordinate to other forms of integration. Moreover, immigrants are described as inherently mistrusting of politics, both due to their political socialization and current US politics. Thus, this study sheds further light on how local politicians interpret immigrant political integration in the USA.
Keywords: 300; Political integration; Local politics; Qualitative methods; USA